2005
DOI: 10.1152/ajpendo.00201.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of recombinant CYP2C11: a vitamin D 25-hydroxylase and 24-hydroxylase

Abstract: Studies were performed to further characterize the male-specific hepatic recombinant microsomal vitamin D 25-hydroxlase CYP2C11, expressed in baculovirus-infected insect cells, and determine whether it is also a vitamin D 24-hydroxylase. 25-and 24-hydroxylase activities were compared with those of 10 other recombinant hepatic microsomal cytochrome P-450 enzymes expressed in baculovirus-infected insect cells. Each of them 25-hydroxylated vitamin D 2, vitamin D3, 1␣-hydroxyvitamin D2 (1␣OHD2), and 1␣-hydroxyvita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 33 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…CYP2C11 is expressed in the liver of male rats. It has 25-hydroxylase activity for D 3 and D 2 as well as the 1OHD analogs but is better known for its hydroxylations of testosterone (Rahmaniyan et al, 2005). It is not clear if there is a human homolog.…”
Section: Vitamin D Metabolismmentioning
confidence: 99%
“…CYP2C11 is expressed in the liver of male rats. It has 25-hydroxylase activity for D 3 and D 2 as well as the 1OHD analogs but is better known for its hydroxylations of testosterone (Rahmaniyan et al, 2005). It is not clear if there is a human homolog.…”
Section: Vitamin D Metabolismmentioning
confidence: 99%
“…with a high K M relative to physiological substrate concentration) (30) . CYP2J3 (34) , CYP2D25 and CYP2C11 also show VD 25-hydroxylase activity but are only expressed in pigs and male rats, respectively (35,36) . 25-Hydroxylation seems to be functional in adipose tissue, as Zoico et al (37) recently reported that 25(OH) D release in the cell culture medium increased after 24 h incubation of 3T3-L1 adipocytes with VD.…”
Section: -Hydroxylationmentioning
confidence: 99%
“…18 Reports have suggested that the presence of microsomal CYP (CYP2R1) and the mitochondrial CYP27A 22 acts as 25-hydroxylases. [23][24][25][26] Thus, it is possible that local concentrations of the active metabolites of 1"(OH)D 2 are higher at various tissue sites that are rich in the activation enzymes. The effect of 1"(OH)D 2 on its target genes is expected to be higher in the kidney because Cyp24 activates, rather than deactivates, 1"(OH)D 2 in contrast to the catabolism of 1,25(OH) 2 D 3 to form the inactive 1,24,25(OH) 3 D 3 .…”
Section: Introductionmentioning
confidence: 99%